2018
DOI: 10.1063/1.5037721
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature high-sensitivity AlN-on-SOI Lamb wave resonant strain sensor

Abstract: A piezoelectric AlN-on-SOI structured MEMS Lamb wave resonator (LWR) is presented for high-temperature strain measurement. The LWR has a composite membrane of a 1 μm thick AlN film and a 30 μm thick device silicon layer. The excited acoustic waves include Rayleigh wave and Lamb waves. A tensile strain sensor has been prepared with one LWR mounted on a uniaxial tensile plate, and its temperature characteristics from 15.4°C to 250°C and tensile strain behaviors from 0 με to 400 με of Rayleigh wave and S4 mode La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Table 1 presents a comparison of the sensor developed in this study with previously reported sensors [ 15 , 36 , 38 , 39 ]. The sensor proposed herein has the following advantages: The strain range is sufficiently large to monitor a relatively larger range of strain changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 presents a comparison of the sensor developed in this study with previously reported sensors [ 15 , 36 , 38 , 39 ]. The sensor proposed herein has the following advantages: The strain range is sufficiently large to monitor a relatively larger range of strain changes.…”
Section: Resultsmentioning
confidence: 99%
“…When the sensor is placed in a temperature-strain compound environment, put the temperature value into the formula to get the effect of temperature on strain, and then get the actual strain value. Table 1 presents a comparison of the sensor developed in this study with previously reported sensors [15,36,38,39]. The sensor proposed herein has the following advantages: Table 1 presents a comparison of the sensor developed in this study with previously reported sensors [15,36,38,39].…”
Section: Temperature Testmentioning
confidence: 99%
“…73–85 The nanofabrication technologies for preparing SEIRA/SERS substrates include chemical preparation methods, photolithography, electron beam lithography, magnetron sputtering, electron beam evaporation, and more. 86–107 The widely used theory for modeling SERS/SEIRA includes perturbation theory, 108 temporal coupled-mode theory, 109,110 coupled harmonic oscillator theory, 111 and so on. As mentioned earlier, machine learning is complementary to SERS/SEIRA and offers unparalleled possibilities for solving pressing challenges related to spectral artifacts, overlapping, and huge volumes of spectral data (Fig.…”
Section: Concept Of Machine Learning Enhancing Sers and Seiramentioning
confidence: 99%
“…Recently, various electro-acoustic devices based on aluminum nitride thin film technology have also been proposed for frequency control and sensing applications at high temperature [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Some of these devices are based on bulk acoustic waves (BAW), following either thin-film bulk acoustic resonator technologies (FBAR), or solidly mounted resonator technologies (SMR) [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%